The Relationship between Agricultural Extension Officer (PPL) Activities and Facilities and the Capabilities of Farmer Groups in Kalipuro District, Banyuwangi Regency - Adyla Mita Lestari; Adita Windasari; Muhandoyo Muhandoyo; Juli Rahaju; Umi Afdah (Journal of Universal Community Empowerment Provision, 2026)
The purpose of extension activities is to change individual or community attitudes, including knowledge, skills, and mental attitudes. Margono Slamet (1978) states that changing attitudes requires extension efforts through information dissemination. With the willingness and ability to improve their practices, farmers are expected to increase agricultural production, achieve better profitability, and improve their quality of life. This study examines the relationship between facilities and the activities of agricultural extension workers (PPL), as well as the relationship between PPL activities and the capacity of farmer groups. The results are expected to enhance the effectiveness of PPL activities and improve farmer group performance. The findings from the Agricultural Extension Center (BPP) in Kalipuro District show that: (1) PPL activities are relatively high; (2) farmer group capacity is also relatively high due to strong farmer responsiveness; and (3) facilities such as library conditions, training infrastructure, and skill development are related to PPL activity levels. Additionally, incentive perceptions and group capacity are associated with PPL activities. Chi-square analysis indicates that all variables (library, infrastructure, skills, perceptions, and group capacity) have significant relationships with PPL activities (X² calculated > X² table), meaning the null hypothesis is rejected. Thus, there is a significant relationship between facilities and PPL activities on farmer group capacity. It is recommended that PPL intensify extension efforts to further improve farmer productivity and group performance.